Analisis Model Score (Stimulus, Capability, Collusion, Opportunity, Rationalization dan Ego) Terhadap Korupsi: Studi Pada Pemerintah Provinsi di Indonesia Tahun 2018-2022 - Yane Nurhaliezah; Rusmianto Rusmianto; Destia Pentiana (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
Corruption refers to an unlawful act that involves the misuse of authority to benefit an organization while causing harm to the state's economy. This research aims to examine the impact of stimulus, capability, collusion, opportunity, rationalization, and ego on corruption within provincial governments in Indonesia during the 2018-2022 period. The study population consists of all provinces in Indonesia. The sample selection was conducted using the purposive sampling method. Based on this approach, 34 provincial governments met the criteria for inclusion in the study. To test the hypotheses, this research employs IBM SPSS software version 26, utilizing the logistic regression analysis method. The findings indicate that, in part, capability and opportunity positively influence corruption, while rationalization and ego have a negative effect. Meanwhile, stimulus and collusion do not significantly impact corruption.